Accuracy study of a robotic system for MRI‐guided prostate needle placement. Issue 3 (8th June 2012) - Seifabadi, Reza; Cho, Nathan B. J.; Song, Sang‐Eun; Tokuda, Junichi; Hata, Nobuhiko; Tempany, Clare M.; Fichtinger, Gabor; Iordachita, Iulian
Abstract Background Accurate needle placement is the first concern in percutaneous MRI‐guided prostate interventions. In this phantom study, different sources contributing to the overall needle placement error of a MRI‐guided robot for prostate biopsy have been identified, quantified and minimized to the possible extent. Methods The overall needle placement error of the system was evaluated in a prostate phantom. This error was broken into two parts: the error associated with the robotic system (called 'before‐insertion error') and the error associated with needle–tissue interaction (called 'due‐to‐insertion error'). Before‐insertion error was measured directly in a soft phantom and different sources contributing into this part were identified and quantified. A calibration methodology was developed to minimize the 4‐DOF manipulator's error. The due‐to‐insertion error was indirectly approximated by comparing the overall error and the before‐insertion error. The effect of sterilization on the manipulator's accuracy and repeatability was also studied. Results The average overall system error in the phantom study was 2.5 mm (STD = 1.1 mm). The average robotic system error in the Super Soft plastic phantom was 1.3 mm (STD = 0.7 mm). Assuming orthogonal error components, the needle–tissue interaction error was found to be approximately 2.13 mm, thus making a larger contribution to the overall error. The average susceptibility artifact shift was 0.2 mm. The manipulator's targeting accuracy was 0.71 mm (STD = 0.21 mm) after robot calibration. The robot's repeatability was 0.13 mm. Sterilization had no noticeable influence on the robot's accuracy and repeatability. Conclusions The experimental methodology presented in this paper may help researchers to identify, quantify and minimize different sources contributing into the overall needle placement error of an MRI‐guided robotic system for prostate needle placement. In the robotic system analysed here, the overall error of the studied system remained within the acceptable range. Copyright © 2012 John Wiley & Sons, Ltd.